EVALUATION OF PROJECT-BASED LEARNING IN SOCIAL SCIENCES LEARNING SUBJECTS IN ELEMENTARY SCHOOLS - Nora, Yulfia; Ambiyar; Aziz, Ishak (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
The implementation of project-based learning in social sciences learning subjects contains learning material regarding the types of social institutions, religion, economics, and politics. The purpose of this paper is to describe the evaluation of project-based learning in social science learning subjects in elementary schools. The method used is a literature review with a meta-analysis of ten national-indexed journal review results based on the evaluation of project-based learning on learning subjects in elementary schools. The research results were grouped and analyzed based on the evaluation of project-based learning in social sciences learning subjects in elementary schools. The analysis results of a number of research indicate that there are (a) inadequacies of teacher skills in the use of learning models that encourage students in the learning process, (b) inadequate learning media used in social sciences learning subjects, (c) still using conventional teaching method in teaching and learning process so that students do not achieve the results from learning, and (d) insufficient teacher’s competence in the implementation of project-based learning in social sciences learning subjects in elementary schools. Through the four results of the evaluation of social sciences learning subjects in elementary schools, Students’ independence and discipline can increase so that they can communicate and achieve learning objectives.